Оптимальное обнаружение сигналов на фоне микросейсмического шума - Мостовой, В.С. (Видавничий дім "Академперіодика" НАН України, 2008)
The problem of signal detection on a microseismic background noise is of current importance, but especially in analysis of those signals which are comparable or smaller than the level of background noise from the energetic point of view. Background noise establishes a natural restriction to the signals that can be detected by seismic tools. Under condition of a high-level
noise, the conceptual mathematical model of optimal estimation of the signal parameters is proposed. Efficiency of the model is illustrated by the example of a field observation experiment.